2023
DOI: 10.1111/pce.14710
|View full text |Cite
|
Sign up to set email alerts
|

Dark respiration explains nocturnal stomatal conductance in rice regardless of drought and nutrient stress

Yulin Yan,
Youngryel Ryu,
Benjamin Dechant
et al.

Abstract: The ecological mechanism underlying nocturnal stomatal conductance (gsn) in C3 and C4 plants remains elusive. In this study, we proposed a ‘coordinated leaf trait’ hypothesis to explain gsn in rice plants. We conducted an open‐field experiment by applying drought, nutrient stress and the combined drought–nutrient stress. We found that gsn was neither strongly reduced by drought nor consistently increased by nutrient stress. With the aforementioned multiple abiotic stressors considered as random effects, gsn ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…than normally observed at night (Resco de Dios et al, 2019). During daytime, leaf R D appears necessary in terms of energy for changes in g s (Vialet-Chabrand et al, 2021) and perhaps this is also the case at night (Yan et al, 2023).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…than normally observed at night (Resco de Dios et al, 2019). During daytime, leaf R D appears necessary in terms of energy for changes in g s (Vialet-Chabrand et al, 2021) and perhaps this is also the case at night (Yan et al, 2023).…”
Section: Resultsmentioning
confidence: 87%
“…However, we agree with Resco de Dios et al (2019) that this cannot be the sole reason for nocturnal g s above zero, as it requires much higher levels of [CO 2 ] to significantly inhibit plant respiration (Bruhn et al, 2002, 2007) than normally observed at night (Resco de Dios et al, 2019). During daytime, leaf R D appears necessary in terms of energy for changes in g s (Vialet‐Chabrand et al, 2021) and perhaps this is also the case at night (Yan et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Maize plants are C4 plants ( Bellasio et al., 2023 ) more suited to hot climates while rice plants are C3 plants which grow in cool environments ( Bellasio et al., 2019 ; Osinde et al., 2023 ). Oryza sativa normally grows emerged in water ( Yan et al., 2023 ), whereas Zea mays grows under more dry conditions on land. Differences in the charge distributions of Zm Chi19A and Os Chi19A may be adaptations to specific ecological niches, lifestyles, or host-pathogen interactions ( Vanhoye et al., 2004 ; Garcia-Moreno, 2009 ; Gerland et al., 2020 ; Kim et al., 2020 ; Panja et al., 2020 ; Di Savino et al., 2021 ; Doan et al., 2022 ; Vallina Estrada et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%